Knowledge, attitudes and practices regarding wild animal trade and consumption in the prevention of zoonotic diseases among students at a public university - Zainul Azlan, Nurhazirah; Wan Abas, Wan Norzarifah; Razaly, Nur Nabilah Shahirah; Othman, Noratikah; Jainlabdin, Mohd Hanif; Md Isa, Muhammad Lokman (IIUM Press, 2025)
Zoonotic diseases are infections transmitted from animals to humans and pose growing public health concerns globally. The trade and consumption of wild animals are key risk factors contributing to the emergence of zoonotic diseases. The objective of this study is to determine the level of knowledge, attitudes, and practices among undergraduate students at the International Islamic University Malaysia (IIUM), Kuantan Campus, Pahang, regarding wild animal trade and consumption in the prevention of zoonotic diseases, as well as their association with sociodemographic characteristics. A cross-sectional study using convenience sampling was conducted among 196 undergraduate students from April to May 2022. An English version of the questionnaire was administered, and data were analysed using SPSS Version 20. The results showed that most students had high levels of knowledge (75.5%), attitudes (94.9%), and practices (96.0%) regarding the prevention of zoonotic diseases. Additionally, significant associations were observed between knowledge level and age, as well as year of study and courses (p-value<0.05). These findings suggest the effectiveness of current educational exposure and highlight the need for tailored awareness initiatives to other populations. Educational interventions, grounded in both scientific knowledge and Islamic values, can further enhance public awareness and promote responsible practices regarding wild animal trade and consumption.